A simulated annealing algorithm for transient optimization in gas networks - Mahlke, Debora; Martin, Alexander; Moritz, Susanne (Mathematical Methods of Operations Research, 2007)
In this paper we present a simulated annealing approach for the gas network optimization problem. A gas network consists of a set of pipes to transport the gas from the sources to the sinks whereby gas pressure gets lost due to friction. Further on there are compressors, which increase gas pressure, and valves. The aim is to minimize fuel gas consumption of the compressors whereas demands of consumers have to be satisfied. The problem of transient (time-dependent) optimization of gas networks results in a highly complex mixed integer nonlinear program. We relax the equations describing the gas dynamic in pipes by adding these constraints combined with appropriate penalty factors to the objective function. A suitable neighborhood structure is developed for the relaxed problem where time steps as well as pressure and flow of the gas are decoupled. Our approach convinces with flexibility and very good computational results.
Keywords: Heuristics; Mixed integer nonlinear programming; Relaxation; Simulated annealing; Transient gas optimization